Литовско-славянские лексические параллели (на материале восточнославянских и южнославянских языков) - Павловна Васильева, Людмила; Радакович, Нинослав (Slavistica Vilnensis, 2009)
The Baltic-Slavic relationship goes back to ancient times. The existence of parallels between Lithuanian and various Slavic languages draws great attention. Words and expressions that were once common to Lithuanians and Slavs have either disappeared (in Lithuanian and in one of the Slavic languages) or have changed their meaning. Аt present Lithuanian and East or South Slavic parallels are sometimes easy to identify, sometimes difficult, and in some cases virtually impossible. The article investigates the use of related words in East Slavic, South Slavic and Baltic languages.